Analisis Strategi Pemasaran terhadap Peningkatan Penjualan pada UMKM Kebab Rendang - Revita Sari (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2022)
This research discusses the analysis of marketing strategies to increase sales at UMKM Kebab Rendang in Medan City, the type of research used is a qualitative method with interview data collection techniques, and documentation is carried out to obtain data, the focus of this research is what marketing strategies should be carried out to increase sales MSME products (case study on Kebab Rendang)? The research results show that marketing strategy management includes: 1) segmentation, 2) targeting, 3) positioning, 4) Marketing mix. The results above are concluded as follows: Marketing strategy analysis to increase sales is currently effective with the components of segmentation, targeting, positioning and marketing mix so that it is able to increase sales